Polish Traditions of Adult Education Institutions in the Context of Lifelong Learning - Agnieszka Stopińska-Pająk (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2016)
An article presents Polish institutions dedicated to adult education from the 19th century and the beginning of 20th century that are a part of the lifelong learning concept which is so common and well-recognised currently. The aim of the article is to show that lifelong learning is not a new phenomenon; rather a well-established one. The need for andragogical historical research on the development of Polish adult education institutions, especially institutions, in which the adults could experience learning, is discussed along with the methodological comments. The article presents some selected adult education institutions; 1. Institutions connected to the self-education movement from the 19th century; 2. Type of common university - the Flying University, which developed from the before mentioned movement; 3. Higher schools for adults; 4. Folk high schools; and, 5. Day rooms for adults. The institutions exemplify the changes in the way the term learning was understood; from fulfilling the cognitive needs, through the needs of social engagement to the cultural, social and ludic needs. On the other hand, they are the examples of gradual enlargement of circles involved in those learning institutions; from the intelligence to blue-collar workers and farmers, from men to women, from those highly ranked in social stratification to those ranked much lower.